An Intellectual Foundation for the Grammatical Sentence in Arabic - Alhawawshah , Mahmoud (Dirasat: Human and Social Sciences, 2022)
This research paper discusses the intellectual foundation present in the grammatical structure of the verbal and nominal sentences in Arabic by identifying and analyzing specific intellectual foundation evidence that goes in line with the Islamic idea of monotheism based on the notion of the presence of factors, subject, adjuncts, predication, diacritics etc. The introduction discusses the concept of language and its origins. The findings helped explain the origin of Arabic language, and its creation. It also discussed the idea whether Arabs belong to the Arabic Language or vice versa. The body of the research paper included the intellectual foundation for of Arabic sentence structure. Evidence included the idea of the factor that affects other parts of the sentence, which is fundamental in syntax. It explained the importance of the subject in the structure of the verbal sentence grammar. This idea agrees with the idea that everything is caused by a cause. Examples include the presence of adjuncts and the passive voice where a subject (causer) is present although it is unknown. The findings show that sentence in Arabic is based on the idea of monotheism and that the origin of the Arabic language far exceeds other languages. The findings also show that Arabic is a representation of a monotheistic society or that it is of a divine source.